Strategi Guru Pendidikan Agama Islam dalam Membina dan Membentuk Akhlakul Karimah Siswa SMP Islam - Putri, Ayu Qinaroh Khoridatun Nafisah (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Education for humanity is a system and way to improve the quality of life in all fields. In the history of human life on this earth, there is almost no group of human beings that does not use education as a means of civilizing and improving their quality, even in primitive groups. It's just that the systems and methods vary according to the standard of living and culture of each community. This research uses qualitative research. This research focuses on the strategies of Islamic religious education teachers in developing and forming students' morals at the Nurul Mukminin Islamic Junior High School, Baletbaru Village, Sukowono District, Jember Regency. The data collection technique is observation, interviews and documentation. The aim of this research is to find out PAI teachers' strategies in developing and forming students' morals at Nurul Mukminin Islamic Junior High School, Baletbaru Village, Sukowono District, Jember Regency. Meanwhile, the conclusions and results of this research indicate that the moral condition of students at the Nurul Mukminin Islamic Junior High School, Baletbaru Village, Sukowono District, Jember Regency in their attitude, behavior and language in general is quite good. The strategy used by Islamic religious education teachers in forming and developing students' morals at Nurul Mukminin Islamic Junior High School, Baletbaru Village, Sukowono District, Jember Regency, is by example and habituation methods, as well as preparing activity programs that can help in developing students' morals.